Analysis of the association between lactotransferrin (LTF) gene polymorphism and dental caries (Journal of Applied Oral Science, 2010)
OBJECTIVE: The present study evaluated the association between lactotransferrin (LTF) gene polymorphism (exon 2, A/G, Lys/Arg) and dental caries. MATERIAL AND METHODS: A convenience sample of 110 individuals, 12 years old, was divided into: group 1, 48 individuals without caries experience (DMFT=0), and group 2, 62 subjects with caries experience (DMFT>;1). DNA was obtained from a mouthwash with 3% glucose solution, followed by a scrapping of the oral mucosa. After DNA purification, polymerase chain reaction (PCR), single strand conformation polymorphism (SSCP) was performed to access the study polymorphism. The LTF A/G (Lys/Arg) polymorphism had been previously reported as located in exon 1. RESULTS: Allele 1 of the study polymorphism was associated with low DMFT index and showed a protective effect against caries experience (OR=0.16, IC=0.03-0.76, p=0.01). CONCLUSIONS: Lactotransferrin A/G (exon 2, Lys/Arg) polymorphism was associated with susceptibility to dental caries in 12-year-old students.